2022
DOI: 10.3390/rs14081881
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Atmospheric Correction Algorithms Applied to OLCI Sentinel-3 Data of Chesapeake Bay Waters

Abstract: Satellite remote sensing permits large-scale monitoring of coastal waters through synoptic measurements of water-leaving radiance that can be scaled to relevant water quality metrics and in turn help inform local and regional responses to a variety of stressors. As both the incident and water-leaving radiance are affected by interactions with the intervening atmosphere, the efficacy of atmospheric correction algorithms is essential to derive accurate water-leaving radiometry. Modern ocean color satellite senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 83 publications
2
7
0
Order By: Relevance
“…These results are consistent with other studies showing that Polymer has superior performance for OLCI retrievals in coastal waters (e.g., Alikas et al., 2020; Juhls et al., 2022; Pahlevan et al., 2020; Sherman, Tzortziou, Turner, Goes, & Grunert, 2023). Yet, other studies suggested that different approaches, such as C2RCC and ACOLITE, perform better in highly turbid and eutrophic environments (Giannini et al., 2021; Mograne et al., 2019; Vanhellemont & Ruddick, 2021; Windle et al., 2022), highlighting the need for more studies to assess the robustness of AC algorithms across a range of atmospheric and in‐water conditions. Based on the superior performance of Polymer across a range of conditions in the highly dynamic LIS, Polymer was selected as the preferred AC approach for subsequent processing of all OLCI L1B images.…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with other studies showing that Polymer has superior performance for OLCI retrievals in coastal waters (e.g., Alikas et al., 2020; Juhls et al., 2022; Pahlevan et al., 2020; Sherman, Tzortziou, Turner, Goes, & Grunert, 2023). Yet, other studies suggested that different approaches, such as C2RCC and ACOLITE, perform better in highly turbid and eutrophic environments (Giannini et al., 2021; Mograne et al., 2019; Vanhellemont & Ruddick, 2021; Windle et al., 2022), highlighting the need for more studies to assess the robustness of AC algorithms across a range of atmospheric and in‐water conditions. Based on the superior performance of Polymer across a range of conditions in the highly dynamic LIS, Polymer was selected as the preferred AC approach for subsequent processing of all OLCI L1B images.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the validation process showed that the performance of the algorithms varied according to each spectral band and evaluation metrics. Windle et al (2022) [129] tried to evaluate AC algorithms applied to OLCI Sentinel-3 data of Chesapeake Bay Waters. This sensor takes advantage of higher spatial (300 m), spectral (21 bands), and temporal (2-day) resolutions in coastal water bodies than in any other operational ocean color satellite sensor.…”
Section: Atmospheric Correctionmentioning
confidence: 99%
“…These results are consistent with the findings of Ilori et al ( 2019) who compared different atmospheric correction methods over optically complex coastal waters using in situ radiometric measurements from the Aerosol Robotic Network-Ocean Color (AERONET-OC). Future work could investigate other atmospheric correction algorithms such as Case 2 Regional CoastColour (C2RCC) and POLYnomial-based algorithm applied to Medium Resolution Imaging Spectrometer (POLYMER) in this water body as was done in the Chesapeake Bay (Windle et al, 2022).…”
Section: Satellite Overestimation Of Z Sdmentioning
confidence: 99%